Pengaruh Good.Corporate.Governance,.Profitabilitas, Dan Media Exposure Terhadap.Environmental Disclosure - Amelia, Risca Della; Trisnaningsih, Sri (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
This study was conducted to prove the effect of managerial ownership, institutional ownership, independent commissioners, board size, profitability, and media exposure on environmental disclosure. The method used is quantitative with secondary data. The data came from the official website of each sample company and the official website of the Indonesia Stock Exchange. The population includes companies listed in 2015-2019 on the Indonesia Stock Exchange. The sample method used purposive sampling and obtained 20 companies. Multiple linear regression test is used as a method of analysis with the help of the IBM SPSS version 22 application program.The results show that environmental disclosure is influenced by institutional ownership and media exposure variables. Meanwhile, other variables such as managerial ownership, independent commissioners, board size, and profitability have no effect on environmental disclosure.Â Â